Challenges and Solutions of Discipline in Contemporary Classroom Education - Cristina Ispas; Ana-Maria Eugenia Ispas (Babes-Bolyai University, 2024)
The concept of classroom discipline refers to the various techniques utilized by educators to regulate the conduct and dispositions of pupils throughout the educational experience, with the aim of promoting compliance with institutional standards and fostering a secure, structured, and stimulating milieu conducive to learning. This article investigates the current methodologies and obstacles encountered by modern educational institutions in effectively addressing classroom behavior management. This article examines the perspectives of aspiring and novice educators on the significance of discipline within the classroom setting. It underscores the criticality of effective communication and collaboration among educational institutions, families, and communities in fostering a conducive and inspiring learning atmosphere. This article examines the perspectives of students in the field of education sciences and novice teachers on the origins of inappropriate student behavior and its impact on the educational process within the school setting. Additionally, the article suggests effective strategies and techniques for fostering responsible and appropriate behavior in the classroom. The article underscores the significance of both initial and continuous professional development in effectively managing student behavior, as well as preventing and addressing incidents of school violence.